IMPLEMENTASI KURIKULUM MERDEKA DALAM MENINGKATKAN KREATIVITAS DAN KEMANDIRIAN SISWA: KAJIAN PUSTAKA BERBASIS KEBIJAKAN DAN PRAKTIK PEMBELAJARAN - Suhari, Suhari; Misahradarsi Dongoran (Prosiding Seminar Nasional Indonesia, 2025)
This study aims to analyse the implementation of the Merdeka Curriculum in the context of enhancing student creativity and independence through a literature review focusing on national policies and learning practices in the field. The Merdeka Curriculum is designed to provide flexibility to schools and teachers in developing a more contextual, student-centred, and project-based learning process, thereby optimally fostering the creative potential and independence of students. A review of policy documents, scientific literature, and case studies shows that the implementation of this curriculum has had a positive impact in the form of increased learning motivation, critical thinking skills, and the acquisition of independent learning management skills. However, the success of its implementation still depends on teacher readiness, resource support, and the involvement of various stakeholders. This study recommends improving teacher training, strengthening learning facilities, and conducting continuous evaluations to ensure the effectiveness of the Merdeka Curriculum in realising the goals of 21st-century education.